2019
DOI: 10.1073/pnas.1906717116
|View full text |Cite
|
Sign up to set email alerts
|

A structure-based rationale for sialic acid independent host-cell entry of Sosuga virus

Abstract: The bat-borne paramyxovirus, Sosuga virus (SosV), is one of many paramyxoviruses recently identified and classified within the newly established genus Pararubulavirus, family Paramyxoviridae. The envelope surface of SosV presents a receptor-binding protein (RBP), SosV-RBP, which facilitates host-cell attachment and entry. Unlike closely related hemagglutinin neuraminidase RBPs from other genera of the Paramyxoviridae, SosV-RBP and other pararubulavirus RBPs lack many of the stringently conserved residues requi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
22
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(23 citation statements)
references
References 95 publications
(190 reference statements)
1
22
0
Order By: Relevance
“…It seems likely that SBPA will continue to play an important role in characterizing and rationalizing the pathobiological features of newly emerging viruses. Indeed, we have shown that this is possible for emerging paramyxoviruses, where the receptor-binding domain, an important determinant of host cell tropism, structurally classifies according to receptor specificity (Rissanen et al 2017;Stelfox and Bowden 2019;Pryce et al 2020) (Fig. 2B).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…It seems likely that SBPA will continue to play an important role in characterizing and rationalizing the pathobiological features of newly emerging viruses. Indeed, we have shown that this is possible for emerging paramyxoviruses, where the receptor-binding domain, an important determinant of host cell tropism, structurally classifies according to receptor specificity (Rissanen et al 2017;Stelfox and Bowden 2019;Pryce et al 2020) (Fig. 2B).…”
Section: Discussionmentioning
confidence: 99%
“…HN RBPs bind and hydrolyze sialic acid (Villar and Barroso 2006), H RBPs are presented by morbilliviruses and recognize SLAMF1 and nectin-4 receptors (Bieringer et al 2013;Birch et al 2013;Noyce, Delpeut, and Richardson 2013;Sakai et al 2013;Melia et al 2014;Ader-Ebert et al 2015;Alves et al 2015;Feng et al 2016;Khosravi et al 2016), and most henipaviral G RBPs are specific to ephrin receptors (Bonaparte et al 2005;Negrete et al 2005;Bowden, Jones, and Stuart 2011;Pernet, Wang, and Lee 2012;Rissanen et al 2017). SBPA of known paramyxoviral HN, H, and G RBP structures has shown that these viral proteins segregate according to receptor-specificity (Bowden et al 2008;Lee et al 2015;Rissanen et al 2017;Stelfox and Bowden 2019;Pryce et al 2020) (Fig. 2B).…”
Section: Paramyxovirus Rbps: Pathways To Unique Viral Tropism Charactmentioning
confidence: 99%
See 2 more Smart Citations
“…Finally, remaining members of the Orthoparamyxovirinae, that do not express HN or H proteins, possess G proteins that are either experimentally confirmed or predicted to bind proteinaceous receptors [28][29][30][31][32][33]. More recently, the RBP from members of the Pararubulavirus genera (e.g., Sosuga virus), presumed to contain HN activity, has been shown to not use SA-based receptors [34] (Figure 2 and below for more detailed discussion). The RBP binds the host receptor on the target cell.…”
Section: Introductionmentioning
confidence: 99%